2019
DOI: 10.1042/bst20190221
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow niche crosses paths with BMPs: a road to protection and persistence in CML

Abstract: Chronic myeloid leukaemia (CML) is a paradigm of precision medicine, being one of the first cancers to be treated with targeted therapy. This has revolutionised CML therapy and patient outcome, with high survival rates. However, this now means an ever-increasing number of patients are living with the disease on life-long tyrosine kinase inhibitor (TKI) therapy, with most patients anticipated to have near normal life expectancy. Unfortunately, in a significant number of patients, TKIs are not curative. This low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 215 publications
(257 reference statements)
0
6
0
Order By: Relevance
“…Evidence for this potentially occurring in AML, comes from findings showing that most of these factors are elevated in BM plasma and/or blood plasma of AML patients especially IL-6, CCL2, with a corresponding increase in M2-like CD206 + monocytes and M2-like CD163 + CD206 + Mφs ( Table 1 ) occurring in the BM of AML patients ( Mazur et al, 2007 ; Mussai et al, 2013 ; Sanchez-Correa et al, 2013 ; Su et al, 2013 ; Al-Matary et al, 2016 ). It is well-established that fibroblasts and MSCs also significantly contribute towards acquired BMME-driven therapy resistance in leukaemia and in particular AML ( Salman et al, 2015 ; Busch and Wheadon, 2019 ; Boutin et al, 2020 ). However, the impact of immunomodulation via BM infiltrating immune cells, such as monocytes and Mφs on drug resistance in AML, still remains largely unknown.…”
Section: Bone Marrow Niche Co-option/remodeling By Aml Cellsmentioning
confidence: 99%
“…Evidence for this potentially occurring in AML, comes from findings showing that most of these factors are elevated in BM plasma and/or blood plasma of AML patients especially IL-6, CCL2, with a corresponding increase in M2-like CD206 + monocytes and M2-like CD163 + CD206 + Mφs ( Table 1 ) occurring in the BM of AML patients ( Mazur et al, 2007 ; Mussai et al, 2013 ; Sanchez-Correa et al, 2013 ; Su et al, 2013 ; Al-Matary et al, 2016 ). It is well-established that fibroblasts and MSCs also significantly contribute towards acquired BMME-driven therapy resistance in leukaemia and in particular AML ( Salman et al, 2015 ; Busch and Wheadon, 2019 ; Boutin et al, 2020 ). However, the impact of immunomodulation via BM infiltrating immune cells, such as monocytes and Mφs on drug resistance in AML, still remains largely unknown.…”
Section: Bone Marrow Niche Co-option/remodeling By Aml Cellsmentioning
confidence: 99%
“…Indeed, BMP type-1 receptors inhibition has been shown to efficiently impact MIXL1-expressing AML cells (41). Collectively, these data support that targeting the BMP pathway could constitute a new therapeutic tool to decrease the progenitor capacity of LSCs (24,43).…”
Section: Dynamics Of Bmp Signaling Alterations Under the Pressure Of Treatmentmentioning
confidence: 67%
“…Alox12 Inhibition Disrupts NADH Homeostasis and Induces Oxidative Damage in CML Wnt/β-catenin, p53 and BMP pathways have been reported to play essential roles in maintaining BP-CML HSPC functions, including survival and self-renewal. [25][26][27] Although Alox12 inhibition negatively affected BP-CML HSPCs, Alox12 inhibition by ML355 did not affect transcriptional activities of Wnt/β-catenin, p53, and BMP as shown by luciferase reporter assays ( Figure 4A). In contrast, we found that Alox12 inhibition by both ML355 and siRNA knockdown significantly decreased levels of nicotinamide adenine dinucleotide phosphate (NADPH) and its reduced form NADH in K562 and BP-CML HSPCs ( Figure 4B and Figure S2A), suggesting that Alox12 inhibition disrupts NADH homeostasis.…”
mentioning
confidence: 94%